2004
DOI: 10.1002/qsar.200420018
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Approaches Towards Quinazolines, Quinazolinones and Quinazolinediones on Solid Phase

Abstract: Full PaperQuinazolines are a pharmacologically very attractive class of compounds and have shown activity in various assays. Several successfully launched drugs are based on this scaffold. As a consequence, a more intensive exploitation in drug discovery by solid-phase syntheses of quinazoline libraries has been initiated. A diverse array of combinatorial quinazoline syntheses have been published and an increasing effort is to be expected in the near future to provide more efficient solid phase approaches towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…To date, a number of solid-phase approaches to quinazolinones have been developed and the related literature has been reviewed by Vögtle and Marzinzik in 2006. 20 Recently, Ding et al reported an efficient synthesis of 4(3H)quinazolinones in parallel fashion via poly(ethylene glycol) (PEG) supported aza-Wittig reaction (Scheme 8). 21 Commercially available cheap difunctional PEG-4000 was chosen as a soluble polymer support.…”
Section: Aza-wittig Methodology In 4(3h)-quinazolinone Synthesismentioning
confidence: 99%
“…To date, a number of solid-phase approaches to quinazolinones have been developed and the related literature has been reviewed by Vögtle and Marzinzik in 2006. 20 Recently, Ding et al reported an efficient synthesis of 4(3H)quinazolinones in parallel fashion via poly(ethylene glycol) (PEG) supported aza-Wittig reaction (Scheme 8). 21 Commercially available cheap difunctional PEG-4000 was chosen as a soluble polymer support.…”
Section: Aza-wittig Methodology In 4(3h)-quinazolinone Synthesismentioning
confidence: 99%
“…Ketanserin, a selective serotonin receptor antagonist with weak adrenergic receptor blocking properties, is also used as an antihypertensive agent . 1,3-Substituted quinazoline-2,4(1 H ,3 H )-diones have also been evaluated as possible peripheral vasodilators and antihypertensives as well as anti-inflammatory agents . Quinazoline-2,4(1 H ,3 H )-diones are also useful synthetic materials in heterocyclic chemistry …”
Section: Introductionmentioning
confidence: 99%
“…Among them, quinazolines and quinazolinones have drawn special attention due to the broad spectrum of biological activities of their derivatives, including sedative [1][2][3], anticancer [4][5][6][7], antiviral [8][9][10][11][12], antibacterial [13][14][15], antifungal [15,16], anti-inflamatory [15,[17][18][19] and antifibrotic [20,21] activities. Several reviews focused on the synthetic strategies and biological activities of these compounds have been published [22][23][24][25][26][27][28][29]. The significant impact of various functional groups installed into quinazoline/quinazolinone frameworks on pharmacological properties have been proven.…”
Section: Introductionmentioning
confidence: 99%